Appropriate Fascia Pain Management with Active Stretching in Sales Promotion Girls (SPG) in Makassar City in 2017 - Kristamuliana, Kristamuliana; Novianti, Novianti; Wardania, Sarina (Jurnal Kesehatan - STIKes Prima Nusantara, 2018)
The plantar fascia is a tissue that connects the heel to the toes which serve as a vibration damper, supporting the foot and helping a person to walk. Pain that occurs in that tissue that can be caused by several factors one of them is trauma. Trauma can occur because of the habit of using high heels. Pain usually starts from the heel and can cause inflammation called plantar fasciitis. Active stretching is one of the training methods that can be applied to reduce pain in the plantar fascia. This study was to investigate the effect of active stretching to reduce plantar fascia pain. The method used in this study was pre-experimental with one group pre-test and post-test design, the number of samples was 10 people. The sampling method used total sampling in which the number of samples and the population is the same. Wilcoxon Signed Ranks Test result shows the value p = 0.003 or p <0.05 which means there is an effect of active stretching of plantar fascia pain reduction. Therefore, it can be concluded that there is an active stretching effect on decreasing plantar fascia pain.